Hybrid DNA Origami – Graphene Platform for Electrically‐Gated Nanoscale Motion - João D. G. Azevedo; Tiago Queirós; Filipe Camarneiro; Maria João Lopes; João Freitas; Agnes Purwidyantri; Praneetha Sundar Prakash; Soumya Chandrasekhar; Thorsten‐Lars Schmidt; Pedro Alpuim; Jana B. Nieder (Advanced Materials Interfaces)
Abstract A proof‐of‐principle device for axial high‐resolution operation that combines a deoxyribonucleic acid (DNA) origami with a functionalized graphene layer is presented, analyzed by nanoscopy. Along the DNA origami structure, ATTO‐488 fluorophores are bound at specific distances from graphene, from where specific fluorescence lifetime values are expected due to nearfield energy transfer processes. These are characterized by Fluorescence Lifetime Imaging Microscopy (FLIM). Through modulation of the electrostatic potential of graphene under electrical gating, changes in the fluorescence lifetimes are observed. These are understood as the result of changed energy transfer coupling conditions between the fluorophore and graphene's electronic states, combined with a vertical displacement of the DNA origami structure that matches molecular dimensions. A hybrid architecture is provided whose nanoscale operation depends on the applied voltage regime. A potential application of these findings may be envisioned for biocompatible sensing approaches, in medical or environmental sensing.